Applying Bakhtin scholarship on discourse in education: a critical review essay - Eugene Matusov (University of Lower Silesia, 2013)
Recently, Bakhtinian philologists have charged scholars of education with misapplying Bakhtin's scholarship in their field. In this critical essay, Eugene Matusov reviews two recent edited collections relevant to this issue: Arnetha F. Ball and Sarah Warshauer Freedman's Bakhtinian Perspectives on Language, Literacy, and Learning and Bonny Norton and Kelleen Toohey's Critical Pedagogies and Language Learning. He uses these texts to consider whether Bakhtin has been misapplied in education, how and whether Bakhtin's literary scholarship can be useful for education, and how education can inform. Bakhtinian scholarship. Matusov shows that the philologists' critique of educational scholars is grounded but unjustifiably all-encompassing. Finally, he problematizes whether Bakhtin's notions of dialogism and internally persuasive discourse are compatible with institutionalized education.